CuI mediated synthesis of heterocyclic flavone-benzofuran fused derivatives. Issue 23 (7th June 2017) - Parveen, Iram; Ahmed, Naseem
Graphical abstract: Highlights: Intramolecular Ullmann type synthesis. Highly efficient catalysts (CuI) in cross-coupling reactions. Tolerance of different functional groups. Effective for Cl groups. Low catalyst loading and short reaction time. Abstract: An efficient synthetic method of heterocyclic flavone benzofuran fused derivatives is reported in good to excellent yield (75–90%) via Ullmann type coupling reaction. The protocol involves catalytic amount of CuI (10 mol%) and K2 CO3 base for the intramolecular CO bond formation under mild reaction conditions.